ARCHAEOLOGY OF ROADS: A CASE STUDY OF THE 18TH-CENTURY SUROSOWAN–TASIKARDI OLD ROAD IN BANTEN LAMA AS THE SULTAN’S ROAD - Santoso Putro, Destian Pandu Dwicahyo; Assilmi, Ghilman (UI Scholars Hub, 2025)
Archaeological studies on roads in Indonesia remain relatively limited, although international research indicates that roads are not merely transportation infrastructure, but also embody social, political, and symbolic dimensions. A significant example is the ancient road in Banten Lama, which connects the Surosowan Palace with the artificial lake of Tasikardi. This study aims to present archaeological data and identify the distinctive characteristics of royal roads compared to common roads, applying a landscape archaeology approach within a post-processual paradigm. The research stages include data collection, processing, and interpretation through qualitative methods, encompassing literature review and field observation. The analysis shows that the Surosowan–Tasikardi road contains archaeological evidence reflecting the existence of a political entity with mastery of complex irrigation technology and structured road construction. It is concluded that the road functioned not only as a transportation route but also as a means of royal control over territories and resources, thus qualifying as a representative example of a “sultan’s road” in Indonesia.